Socioeconomic Perspective of Shadow Education - Gupta, Annu Sagar (Curtin University, 2021)
This thesis examines Shadow Education, also known as private tutoring from the perspective of Students, Tutors, Parents and Teachers. Data was collected via the study of tutors’ websites, simulation modelling and focus group discussions. Modernistic on-line platforms and text mining methods were employed to analyse the data. Tutors are capitalizing on demand created by high-stake examinations and parental expectations. The social disparity is increasing and free online resources are insufficient to meet students' demands.